2005
DOI: 10.1007/s00441-005-0011-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased progenitor proliferation and apoptotic cell death in the sensory lineage of mice overexpressing N-myc

Abstract: N-myc, a member of the myc family of bHLH transcription factors, is expressed mainly in the nervous system, including derivatives of neural crest cells in the periphery during development, such as the sensory dorsal root ganglion (DRG). Previous studies suggest that N-myc is involved in the proliferation of progenitor cells in the sensory lineage. To address the role of N-myc in the development of peripheral sensory neurons, we have overexpressed N-myc in sensory progenitor cells. The overexpression of N-myc d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…CaBPs have in mouse mainly been studied as markers for the diverse neuron populations, especially during development and in cultures (e.g. [19,20,28,[30][31][32]), but detailed in vivo quantitative and colocalization analyses of adult mDRGs are less common. Nevertheless, Ichikawa et al [50] reported the presence of PV-LI in~5% of adult mDRG NPs.…”
Section: Other Cabps In Drgsmentioning
confidence: 99%
See 1 more Smart Citation
“…CaBPs have in mouse mainly been studied as markers for the diverse neuron populations, especially during development and in cultures (e.g. [19,20,28,[30][31][32]), but detailed in vivo quantitative and colocalization analyses of adult mDRGs are less common. Nevertheless, Ichikawa et al [50] reported the presence of PV-LI in~5% of adult mDRG NPs.…”
Section: Other Cabps In Drgsmentioning
confidence: 99%
“…In addition, the spinal dorsal horn and spinal trigeminal nucleus, regions important for sensory information processing, including pain, have been studied. They include chicken [21][22][23], Xenopus laevis [24], turtle [25], zebra fish [26], dog [27], mouse [28][29][30][31][32] and, most thoroughly, rat [2,21,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. However, caveats of knowledge exist regarding the cellular sites of Scgn mRNA expression and protein distribution in DRGs or spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…Somehow paradoxically, MYCN overexpression might also lead to apoptosis and/or sensitize cells to death [8], [9], [10]. Indeed, MNA NBs are sensitive to chemo- or radiotherapy at diagnosis, and MNA or MYCN overexpressing NB cell lines are more sensitive to apoptosis induced by DNA damaging agents as compared to MYCN single copy (MNSC) cells [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…MYCN overexpression is also directly linked to apoptosis in cell cultures and animal models (12)(13)(14). A largely validated cell system for conditional MYCN overexpression, the SHEP Tet21/N, has extensively been used to show that MYCN sensitizes MYCN single-copy (MNSC) neuroblastoma cells to apoptosis (15,16).…”
Section: Introductionmentioning
confidence: 99%